Clinical characteristics and treatment of chest submammary accessory breasts. Issue 6 (June 2022) - Lee, Sung Ryul; Park, Jin Young
Abstract: Accessory breast tissue is remnant mammary gland tissue resulting from a failure of regression during the embryonic development and can occur anywhere along the mammary ridge. Patients with accessory breast tissue may also have chest submammary accessory breasts, which are rare and painless, but are often removed for cosmetic reasons. Herein, we report the clinical characteristics and treatment of patients with chest submammary accessory breasts. This retrospective study included 104 women who had undergone liposuction for chest submammary accessory breast from January 2014 to December 2019. chest submammary accessory breasts were diagnosed by ultrasonography and physical examination. The overall satisfaction of patients with chest submammary accessory breast was evaluated using a 5-point Likert scale. The mean operation time was mean 20.7 min and the mean liposuction volume was mean 223.3 mL. The overall satisfaction score (incisional scar, pain and cosmesis) 6 months after chest submammary accessory breast liposuction was 4.7 (range 4–5). The chest submammary accessory breast consisted mainly of fatty tissue rather than mammary gland tissue; thus, chest submammary accessory breasts are painless and are treated purely for cosmetic reasons. In conclusion, liposuction is therefore a simple and effective treatment for chest submammary accessory breast.